2016
DOI: 10.1093/infdis/jiw449
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-125b Prevents Cardiac Dysfunction in Polymicrobial Sepsis by Targeting TRAF6-Mediated Nuclear Factor κB Activation and p53-Mediated Apoptotic Signaling

Abstract: Increased myocardial miR-125b expression attenuates sepsis-induced cardiac dysfunction and improves survival. miR-125b may be a target for septic cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 42 publications
(117 reference statements)
4
55
0
Order By: Relevance
“…Previous studies have indicated TRAF6 took critical part in the processes of sepsis-induced cardiac dysfunction(Ma et al . )20, ischemia-reperfusion injury(Liu et al . )21, immunity response to virus infection(Wei et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated TRAF6 took critical part in the processes of sepsis-induced cardiac dysfunction(Ma et al . )20, ischemia-reperfusion injury(Liu et al . )21, immunity response to virus infection(Wei et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse heart, transfection with lentivirus expressing miR-125b significantly attenuates the expression of ICAM-1 and VCAM-1, the accumulation of immune cells, and cardiac dysfunction caused by sepsis. Lentivirus expressing miR-125b also reduces serum TNF-a and IL-1b in mice, which further weakens endothelial inflammation (12).…”
Section: Mirnas Target the Receptor Complex Of Nf-kb Pathwaymentioning
confidence: 99%
“…MiR-146a could function in braking the immunity via suppressing the level of its target gene, resulting in immune cell immaturation and/or inactivation (31). In sepsis-induced cardiac dysfunction, miR-125b suppresses TNF-α and IL-1β by suppressing TRAF6, as well as markedly attenuates the myocardial apoptosis through decreasing the expression of the p53, Bax, and Bak1 (16). MCEMP1 encodes a single-pass transmembrane protein and is involved in regulating MC differentiation or immune responses (32).…”
Section: Discussionmentioning
confidence: 99%
“…Some miRNAs have been characterized as tumor suppressors in cancers and exerted roles via regulating their target genes (14,15). Wang et al speculated miR-125b as a target for septic cardiomyopathy for an increased myocardial miR-125b expression attenuates sepsis-induced cardiac dysfunction and improves the overall survival of patients with sepsis (16). Restored miR-125a expression decreased the cell proliferation, cell cycle progression, and enhanced apoptosis by targeting ErbB in acute myeloid leukemia (17).…”
Section: Introductionmentioning
confidence: 99%